The new IFTaR method of basic Qur'an reading for beginners in Malaysia: a case study among Muslim converts - Abd Karim, Aishah Hanim; Hashim, Rosnani; Hassan, Hilmiah (IIUM Press, 2022)
The skill of reading the Qur'an and its understanding is obligatory and basic for every Muslim including Muslim converts. Three prevalent methods are used in teaching to read the Qur'an in Malaysia, namely, the Muqaddam, the Qiraati, and the Iqra'. The researchers analyzed the three methods in the literature and presented their pedagogical weaknesses. This study examined the Iqra’ Fast Track Rosnani (IFTaR) method of Qur’an reading for beginners by first explaining its theoretical and pedagogical framework and then explores its application among nine Muslim converts for a period of about two months. The study employed the qualitative research method using online in-depth semi-structured interviews via Google Meet and online open-ended written questionnaires via Google Form. The main research question was how do Muslim converts view IFTaR as a method to learn to read the Qur’an? The results of the study showed that the subjects favoured and viewed the IFTaR method positively, since it helped the Muslim converts to recognize hijaiyah letters easily. It was a better and faster method in learning to read Qur’an compared to the other methods which they used previously. They also recommended its use among new converts.